Clinical Features and Outcome of Sickle Cell Disease in a Tertiary Center in Northern Lebanon: A Retrospective Cohort Study in a Local, Hospital-Associated Registry. (4th March 2021) - Inati, Adlette; Al Alam, Chadi; El Ojaimi, Cristel; Hamad, Taghrid; Kanakamedala, Hemanth; Pilipovic, Virginia; Sabah, Ramzieh
Abstract: Sickle cell disease affects more than 30 million people worldwide, including 0.1% of the population in Lebanon. It is characterized by unpredictable and painful vaso-occlusive crises (VOCs) that may lead to serious complications. This study describes the clinical burden of sickle cell disease in a cohort of patients treated at a comprehensive sickle cell disease referral center in Tripoli, Northern Lebanon. Patient demographics, clinical events, treatment, and survival were evaluated from a local, hospital-based registry of 334 sickle cell disease patients treated at the Nini Hospital, Tripoli, Lebanon, between 2009 and 2019. Mean age at sickle cell disease diagnosis and at first clinic visit was 2.9 and 8.5 years, respectively. Pain was the most common clinical event observed among all patients. Over the 10-year follow-up period, 15 (4.5%) patients died. Hydroxyurea (HU) and red blood cell (RBC) transfusions were the most commonly used therapies. One hundred and thirty-one (39.0%) patients were diagnosed with sickle cell disease at the Nini Hospital; the remaining patients were referred to and subsequently followed-up at the Nini Hospital. Eighty-seven (66.0%) Nini Hospital-diagnosed patients experienced a VOC. Seventy-four (85.0%) of these patients with a VOC event required HU during follow-up. Patients with a VOC required more RBC transfusions, cholecystectomy, and splenectomy than non-VOC patients. The high disease burden observed in this population of sickle cell disease patients illustrates a continued, unmet need to both prevent and manage VOC events and other sickle cell disease-associated complications.